A literary relationship between South Africa and Germany: adapting marketing strategies to different cultures - Retief, Anje Danielle (My University, 2017)
Gérard Genette famously noted that paratexts are ‘those liminal devices’, elements, both within and outside the book, that form part of the complex relationship between book, author, publisher, and reader. He determined that titles, forewords, epigraphs, and publishers’ jacket copy are part of a book’s ‘private and public history’. By considering each of these liminal devices in the larger context of marketing strategies, this research report addresses the question of how paratexts are altered to appeal to different markets in different countries – specifically South Africa and Germany – and how this is done in relation to five translated novels: Stadt des Goldes by Norman Ohler; Portrait with Keys by Ivan Vladislavić; Township Blues and Themba by Lutz van Dijk; and Fiela se Kind by Dalene Matthee. The research report argues that the relationship between paratext and reader is of vital importance when it comes to understanding how cultures are perceived by foreign readers. With each comparison between the paratexts of the original and their translated novels, the research report demonstrates that paratextual alterations are predominantly influenced by alterations in time and geography; use or dismissal of clichés and stereotypes; educational value; and either techniques which familiarise or defamiliarise the reader. By uncovering the way novels are marketed to a foreign readership, it becomes possible to uncover why translations occur and how the source-culture is perceived.
Submitted to the Faculty of Humanities in partial fulfillment of the requirements for the degree of M.A (Publishing Studies) University of the Witwatersrand, South Africa, 2017
Keywords: Book industries and trade; Books--Marketing; Publishers and publishing; Fiction--Publishing; Literature publishing; Translating and interpreting; Paratext